Ability of Kaoline Clays in Adsorption of Aniline,P-Nitro Aniline and 0-Toludine - Isha, S.A..; BaÂ·ssan, S.A.; Jahsim, K. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Adsorption of AniLine and some derivatives from aqueous. solution on kaolin clays surface was investigated, The isotherms were of type S3 d S4 according to Giles Classification. The effect of introducing electron withdrawing groups and electron donating Groups in the aromatic ring on the adsorption process has been investigated ; The results showed that the extent of adsorption has been increased as aÂ·result of substitution of groups, and found that the derivatives were less rn adsorption capacity than the adsorption capacity for the uil substituted compound. The effect of the type of thsubstituted, grqup at the same sjte on the adsorption extent of aniline :was found to decrease in the following order: Aniline > o- nitro Aniline > a-Toluidine Adsorption on kaolin surface was examined as afunction of temperature in the range (298-328k) . The extent of adsorption was found to illc(ease with the increase in temperature (Endothermic) Adsorption studies nn kaolin clays surface at different pH values. showed an increase in the fol10wing order according to the pH of solution for aniline and o- tolu. idine : pH 4 >11 > 7 while foro-nitro Aniline showed increase in the fo-lloorder: pH 11 > 4 > 7